Doses de fertilizante aplicadas via fertirrigação e pulverização foliar em alface conduzida em cultivo protegido - Tavore, Rafael Verri (2013)
The objective of this study was to evaluate the effects of doses and two different application forms, these being, fertigation and foliar spraying, of fertilizer in lettuce (Lactuca sativa L.) conducted in protected cultivation. The experiment was set up and conducted in a greenhouse located at the Technical Centre for Irrigation - CTI, belonging to the campus of the State University of Maringá, Maringá, Paraná. The experimental design was completely randomized design with three replications, having been adopted for evaluations a probability level of 5%. For the composition of the treatments, we used the factorial design with two additional witnesses. The treatments consisted of a combination of factors between levels of foliar fertilizer Apport doses (0.05 mL plant-1; 0.10 mL plant-1;0.40 mL plant-1; 0.80 mL plant-1) with forms of product application (fertigation and foliar spraying). The two additional witnesses corresponded to plants that receiving only topdressing nitrogen fertilization with foliar product Nitromax at a dose of 0.31 mL plant-1, and the plants that received this same treatment with fertilizer Apport, in its recommended dosage (0.20 mL plant-1), thus composing the factorial 4 x 2 + 2. Fresh mass and dry mass commercial of aerial part (FMCAP and DMCAP, respectively) and number of leaves commercial (NLC) were the components of production evaluated. It was observed that for the three components, the unfolding of the Apport product doses within the application form fertigated, not resulted in significant differences between treatments. However for the unfolding of doses of the product within the form of foliar application, for variables FMCAP and NLC had significant effect and the best polynomial regression model that adjusted for both traits was decreasing linear. In unfolding forms of application within each dosage, when worked with the fourth dose (highest dose) for the three variables, and also when used the third dose (0.40 mL plant-1), in this case, only for the variable NLC, the best form of application was fertigation. Regarding additional witnesses, the first witness had better results than the second, for the variables FMCAP and NLC. The findings of this study indicate that the foliar fertilizer Apport also can be used for fertigation.